PANTUN AS A MEANS OF INNOVATION IN CREATIVE ECONOMIC ACTIVITIESIN THE LOK BAINTAN FLOATING MARKET, SOUTH KALIMANTAN - Nailiya Nikmah; Julkawait Julkawait; Rusman Irwansyah (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
Almost all people in Indonesia are familiar with rhymes. Starting from children, adolescents to adults know rhymes with various types. Pantun has been a part of people's lives since ancient times until now. People use rhymes according to their needs. In South Kalimantan, in the Banjar cultural repertoire, pantun coexists with oral traditions such as incantations, proverbs, madihin, lamut, mamanda, bapandung and others. Pantun is not only an identity and cultural character but has also become a supporting medium in various areas of the life of the Banjar people (South Kalimantan), including the empowerment of the creative economy. The type of research used is descriptive qualitative with the approach of netnography and literary anthropology.One of the creative economic activities in South Kalimantan is the floating market or floating market. One of the floating market locations that is the center of creative economic activity is the Lok Baintan floating market.